Potential association of COVID-19 and ABO blood group: An Indian study. (September 2021) - Garg, Iti; Srivastava, Swati; Dogra, Vikas; Bargotya, Mona; Bhattar, Sonali; Gupta, Utkarsh; Jain, Shruti; Hussain, Javid; Hembrom, Anju A.; Ghosh, Nilanjana; Kumar, Vinay; Kumar, Bhuvnesh; et al.
Abstract: Coronavirus disease 2019 (COVID-19) transmits from person to person mainly through respiratory droplets and coughing. Infection severity ranges from asymptomatic and mild infection to those with moderate and severe symptoms which may lead to multiple organ failure and mortality. Infection severity largely depends on individual's immune response, age and co-morbidities. Present study categorized COVID-19 infected patients based on their infection severity and linked COVID-19 severity with age, gender and ABO blood group types. Clinical details of 383 COVID-19 patients were collected from Rajiv Gandhi Super Specialty hospital (RGSSH), India; divided into three groups; mild, moderate and severe patients, based on their symptoms. Present analysis revealed that age plays major role in infection severity, as the symptoms are more severe in patients above 45 years. Infection rate was higher in males compared to females. Most patients with A(+ve) and B(+ve) blood group were severely affected compared to those of blood group type O(+ve) and AB(+ve). O(+ve) blood group was least represented in severe patients. Present findings could be helpful in generating awareness amongst the population regarding susceptibility towards the COVID-19 infection. This supportive information would help clinicians and health workers to propose new strategies and tactical solution against COVID-19 infection. Highlights: COVID-19 patients with A(+ve) and B(+ve) blood group exhibit greater disease severity. Blood Group O(+ve) (most prevalent in India) was proportionally less represented in COVID-19 patients. Percentage of male COVID-19 patients is higher in comparison to female COVID-19 patients. Age remains as strong predictor of the COVID-19 risk, elderly population being severely affected. Effect of SARS-CoV-2 is seen across the age and gender of the Indian population.